Clinical TVA-based studies: a general review - Thomas eHabekost (Frontiers in Psychology, 2015)
In combination with whole report and partial report tasks, the Theory of Visual Attention (TVA) can be used to estimate individual differences in five basic attentional parameters: The visual processing speed, the storage capacity of visual short-term memory, the perceptual threshold, the efficiency of top-down selectivity, and the spatial bias of attentional weighting. TVA-based assessment has been used in about 30 studies to investigate attentional deficits in a range of neurological and psychiatric conditions: (a) neglect and simultanagnosia, (b) reading disturbances, (c) aging and neurodegenerative diseases, and most recently (d) neurodevelopmental disorders. The article introduces TVA based assessment, discusses its methodology and psychometric properties, and reviews the progress made in each of the four research fields. The empirical results demonstrate the general usefulness of TVA-based assessment for many types of clinical neuropsychological research. The method’s most important qualities are cognitive specificity and theoretical grounding, but it is also characterized by good reliability and sensitivity to minor deficits. The review concludes by pointing to promising new areas for clinical TVA-based research.